Modelagem numérica de estruturas de contenção atirantadas em areia - Gurgel, John Glennedy Bezerra (2012)
A numerical study on the behavior of tied-back retaining walls in sand, using the finite element method (FEM) is presented. The analyses were performed using the software Plaxis 2D, and were focused on the development of horizontal displacements, horizontal stresses, shear forces and bending moments in the structure during the construction process. Emphasis was placed on the evaluation of wall embedment, tie-back horizontal spacing, wall thickness, and free anchor length on wall behavior. A representative soil profile of a specific region at the City of Natal, Brazil, was used in the numerical analyses. New facilities built on this region often include retaining structures of the same type studied herein. Soil behavior was modeled using the Mohr-Coulomb constitutive model, whereas the structural elements were modeled using the linear elastic model. Shear strength parameters of the soil layers were obtained from direct shear test results conducted with samples collected at the studied site. Deformation parameters were obtained from empirical correlations from SPT test results carried out on the studied site. The results of the numerical analyses revealed that the effect of wall embedment on the investigated parameters is virtually negligible. Conversely, the tie-back horizontal spacing plays an important role on the investigated parameters. The results also demonstrated that the wall thickness significantly affects the wall horizontal displacements, and the shear forces and bending moments within the retaining structure. However, wall thickness was not found to influence horizontal stresses in the structure